2017
DOI: 10.1177/0042098016686493
|View full text |Cite
|
Sign up to set email alerts
|

Examining the dynamics of the interaction between the development of creative industries and urban spatial structure by agent-based modelling: A case study of Nanjing, China

Abstract: Much of the focus of research on creative industries’ influence upon urban land use has been around the investment in specific regeneration projects or flagship developments rather than addressing the nature and location of the infrastructure, networks and agents engaged. In other words, the complexity of the institutional/temporal and spatial interaction among the involved elements is overlooked or not well understood. This paper presents an agent-based model named CID-USST (Creative Industries Development-Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The study sought to find out whether the cultural dimensions of these countries are related to differences in creativity as well as the impact of exposure to multiple cultures on creativity. Liu and Silva (2018) investigated the dynamics of the interaction between the development of creative industries and urban spatial structure by agent-based modeling in Nanjing, China, by outputting a set of adaptive scenarios through time and space. The results reveal that the spatial distribution of both the creative firms and the creative workers is not related to urban economic condition.…”
Section: Creativity and Organisational Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The study sought to find out whether the cultural dimensions of these countries are related to differences in creativity as well as the impact of exposure to multiple cultures on creativity. Liu and Silva (2018) investigated the dynamics of the interaction between the development of creative industries and urban spatial structure by agent-based modeling in Nanjing, China, by outputting a set of adaptive scenarios through time and space. The results reveal that the spatial distribution of both the creative firms and the creative workers is not related to urban economic condition.…”
Section: Creativity and Organisational Efficiencymentioning
confidence: 99%
“…The gap between the developed countries, as they are often called, and the developing/underdeveloped countries is traceable to the level of creativity and innovation of their industries and employees. There is empirical evidence that international cultures have implications on the creative potentials of citizens and industries across nations (Shao et al, 2019;Liu & Silva, 2018;Boix-Domènech & Rausell-Köster, 2018;Lubart, 2010). Boix-Domènech and Rausell-Köster (2018) quantified the direct and indirect impacts of the creative industry and concluded that the creative industry not only has a direct impact on the employment and production, but also contributes to the technological progress and long-term development of the European Union (EU).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Veal [53] considered that urban governance that stimulates culture aiming to provide urban well-being promotes the minimization of negative factors, i.e., the social inequalities caused by elitism. This means that cities' attractiveness depends on a sustainable structure supported by a relevant regional/local network [21,54], by their own resources and by an understanding of cultural strategies as an urban instrument [21]. Realising the potential of own resources includes the provision of regenerated areas for cultural and creative activities [55].…”
Section: Creativity In Citiesmentioning
confidence: 99%
“…Liu and Silva [48] More open job market information can result in more rapid geographical clustering of the creative firms. It can accelerate innovation through knowledge and information spill-over.…”
Section: Paper Key Findingsmentioning
confidence: 99%